Validation of a new questionnaire measure of tinnitus functioning and disability for use in the UK: the Tinnitus Functional Index (TFI) - Fackrell, Kathryn L. (2016)
The Tinnitus Functional Index (TFI) was developed in the USA as a standard for assessing the functional impact of tinnitus based on eight tinnitus-related domains. The finalised 25-item version was never formally validated. This PhD seeks to assess the psychometric properties of the questionnaire and evaluate its suitability as the tool of choice for use in the diagnostic and outcome assessment of tinnitus for clinical and research purposes in the UK.